Unveiling the molecular and cellular links between obstructive sleep apnea-hypopnea syndrome and vascular aging - Wei Liu; Le Zhang; Wenhui Liao; Huiguo Liu; Wukaiyang Liang; Jinhua Yan; Yi Huang; Tao Jiang; Qian Wang; Cuntai Zhang; Peifang Wei (Chinese Medical Journal)
Abstract. Vascular aging (VA) is a common etiology of various chronic diseases and represents a major public health concern. Intermittent hypoxia (IH) associated with obstructive sleep apnea-hypopnea syndrome (OSAHS) is a primary pathological and physiological driver of OSAHS-induced systemic complications. A substantial proportion of OSAHS patients, estimated to be between 40% and 80%, have comorbidities such as hypertension, heart failure, coronary artery disease, pulmonary hypertension, atrial fibrillation, aneurysm, and stroke, all of which are closely associated with VA. This review examines the molecular and cellular features common to both OSAHS and VA, highlighting decreased melatonin secretion, impaired autophagy, increased apoptosis, increased inflammation and pyroptosis, increased oxidative stress, accelerated telomere shortening, accelerated stem cell depletion, metabolic disorders, imbalanced protein homeostasis, epigenetic alterations, and dysregulated neurohormonal signaling. The accumulation and combination of these features may underlie the pathophysiological link between OSAHS and VA, but the exact mechanisms by which OSAHS affects VA may require further investigation. Taken together, these findings suggest that OSAHS may serve as a novel risk factor for VA and related vascular disorders, and that targeting these features may offer therapeutic potential to mitigate the vascular risks associated with OSAHS.